The Meladema Laporte, 1835 (Coleoptera, Dytiscidae) of the Sahara Desert - Ribera, Ignacio; Bilton, David T.; Cardoso, Anabela (Zootaxa, 2018)
Meladema Laporte, 1835 is a genus of large diving beetles, found in the Western Palaearctic, from the Canary Islands and Madeira to western Turkey (Bilton & Ribera 2017). The genus currently contains four species: the widespread M. coriacea Laporte, 1835, distributed from the Canary Islands to Turkey and ranging from southern France and the central Balkans south to the central Sahara, two Atlantic Island endemics, M. imbricata (Wollaston, 1871) from the western Canary Islands and M. lanio (Fabricius, 1775) from the main island of Madeira, and a fourth, recently described species, M. lepidoptera Bilton & Ribera, 2017 from the Tyrrhenian Islands (Corsica, Sardinia, Elba, Montecristo) and parts of the Italian mainland (Bilton & Ribera 2017).